2017
DOI: 10.1002/jms.4026
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and glucosamine mobility shifts by adduction with 2‐butanol depended on interaction energy, charge delocalization, and steric hindrance in ion mobility spectrometry

Abstract: Ion mobility spectrometry (IMS) is an analytical technique that separates gas-phase ions drifting under an electric field according to their size to charge ratio. We used electrospray ionization-drift tube IMS coupled to quadrupole mass spectrometry to measure the mobilities of glucosamine (GH ) and caffeine (CH ) ions in pure nitrogen or when the shift reagent (SR) 2-butanol was introduced in the drift gas at 6.9 mmol m . Binding energies of 2-butanol-ion adducts were calculated using Gaussian 09 at the CAMB3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…In other words, the O‐protomers (isomers b , c , and d ) are less stable than their corresponding N‐protomer (isomers a ). It is in agreement with previous studies reported that nitrogen sites are more basic than the oxygen sites 41,42 . The calculated PAs of the oxygen sites (Table 1) are higher than that of H 2 O (691 kJ mol −1 ), 43 and protonation of these sites in the presence of H 3 O + is thermodynamically favored.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, the O‐protomers (isomers b , c , and d ) are less stable than their corresponding N‐protomer (isomers a ). It is in agreement with previous studies reported that nitrogen sites are more basic than the oxygen sites 41,42 . The calculated PAs of the oxygen sites (Table 1) are higher than that of H 2 O (691 kJ mol −1 ), 43 and protonation of these sites in the presence of H 3 O + is thermodynamically favored.…”
Section: Resultssupporting
confidence: 92%
“…40 is in agreement with previous studies reported that nitrogen sites are more basic than the oxygen sites. 41,42 The calculated PAs of the oxygen sites (Table 1) Figure S4. With NH 3 dopant, the intensities of peaks M2 and C2 attributed to the carbocations of morphine and codeine decreased and the peaks M1 and C1 were observed as the main peaks.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Energy interactions have been used to explain the mobility shift behavior of different ions after injecting SRs in the buffer gas. When ethyl lactate (L, 22 mmol m −3 ) or 2‐butanol (B, 6.9 mmol m −3 ) were used as SRs in ESI‐IMS‐QMS at 150°C and humidity ~10 ppm, the mobility of protonated glucosamine, GH + , was more affected than that of protonated caffeine, CH + , because GH + clustered more. Theoretical calculations showed that the GLH + and GBH + clusters were more energetically stable (−26.30 and −19.9 kcal/mol, respectively) than CLH + and CBH + (−24.66 and −19.5 kcal/mol, respectively) possibly because the positive charge in GH + was more sterically accessible than in CH + for adduction and the charge was stabilized by resonance in CH + .…”
Section: Effect Of Energy Interactions On Mobility Shiftsmentioning
confidence: 99%
“…When dextromethorphan (Dx) and diphenhydramine (Dy) were analyzed with 2‐butanol in the buffer gas, the mobility shift of DxH + was unexpectedly larger than that of DyH + because DxH + showed 2 favorable sites for adduction vs only one in DyH + (see Section 8). Roscioli confirmed that SRs with several interaction sites show the strongest interaction with analyte ions . She found that 2‐ethylhexyl salicylate and ethyl lactate were the SRs producing the largest mobility shifts among 11 SRs including amines, nitriles and nitro groups, and 2‐butanol.…”
Section: Number Of Sites For Adduction and Mobility Shiftsmentioning
confidence: 99%
See 1 more Smart Citation